2003
DOI: 10.1289/ehp.5992
|View full text |Cite
|
Sign up to set email alerts
|

Asthma symptoms in Hispanic children and daily ambient exposures to toxic and criteria air pollutants.

Abstract: Although acute adverse effects on asthma have been frequently found for the U.S. Environmental Protection Agency's principal criteria air pollutants, there is little epidemiologic information on specific hydrocarbons from toxic emission sources. We conducted a panel study of 22 Hispanic children with asthma who were 10-16 years old and living in a Los Angeles community with high traffic density. Subjects filled out symptom diaries daily for up to 3 months (November 1999 through January 2000). Pollutants includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 64 publications
10
121
1
1
Order By: Relevance
“…Three additional articles were excluded because they were not asthma-specific, but rather focused on respiratory symptoms (e.g., chest discomfort) or pulmonary function (Franklin et al 2000;Symington et al 1991;Wantke et al 1996). Two studies were excluded because, although asthma-specific, they did not contain a reference or control group (Delfino et al 2003;Erdei et al 2003). For the 10 articles included, we abstracted information regarding study design and setting, subject response/participation rates, definition of asthma (e.g., physician diagnosis), sample size, average (minimum and maximum) formaldehyde levels, average age of study subjects, and quantitative estimates (or raw data) for the association between formaldehyde exposure and asthma as well as whether such estimates were adjusted and, if so, for what measures (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three additional articles were excluded because they were not asthma-specific, but rather focused on respiratory symptoms (e.g., chest discomfort) or pulmonary function (Franklin et al 2000;Symington et al 1991;Wantke et al 1996). Two studies were excluded because, although asthma-specific, they did not contain a reference or control group (Delfino et al 2003;Erdei et al 2003). For the 10 articles included, we abstracted information regarding study design and setting, subject response/participation rates, definition of asthma (e.g., physician diagnosis), sample size, average (minimum and maximum) formaldehyde levels, average age of study subjects, and quantitative estimates (or raw data) for the association between formaldehyde exposure and asthma as well as whether such estimates were adjusted and, if so, for what measures (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that certain groups, specifically children, may be particularly sensitive to formaldehyde exposure; however, as with adults, the results have been inconsistent, with some studies reporting an association (Garrett et al 1999) and others not (Symington et al 1991). All of these studies have specific limi-tations including small sample sizes (Delfino et al 2003), the use of self-reported asthma (Smedje et al 1997), and potential selection bias (Garrett et al 1999). In addition, the extent of formaldehyde exposure varies widely across studies.…”
mentioning
confidence: 99%
“…Significant associations were mainly observed among symptomatic subjects. In this population, indoor particulate matter concentration has been related to a decrease in lung function, in particular among children with asthma [117][118][119][120] and, to a lesser extent, to an increased risk of asthmatic and bronchitis-like symptoms [121,122]. In a cohort of 150 asthmatic children, PM2.5 and PM2.5-10 concentrations, assessed three times every 3 months, were positively associated with the incidence rate of several respiratory symptoms, including cough, asthma symptoms and wheezing [121].…”
Section: Particulate Mattermentioning
confidence: 99%
“…Though the roles of specific air pollutants on various respiratory illnesses remain unclear (Brunekreef et al, 1995, Delfino et al, 2003, the majority of earlier investigations considered air pollutants a risk factor for asthma. That is, the general effect of air pollution leads to adverse respiratory cases.…”
Section: Auto Correlation Analysesmentioning
confidence: 99%